URGENSI PERPANJANGAN MASA JABATAN NOTARIS DI INDONESIA DIKAITKAN DENGAN PRINSIP RASIONALITAS - Defega, Zena Dinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: There iis ia ivacuum iof inorms iin ithe ilegislation ion ifurther itechnical iregulations irelated ito ithe iextension iof ithe iterm iof iNotary iOffice. iNotaries iwho ireach ithe iage iof i67 imay ibe iconfused iwhether ithey ican iimmediately iextend itheir iterm ito i70 iyears ior ihave ito iwait ifor itechnical irules ifrom ithe iMinistry iof ilaw. iThe iresearch imethod iused iis inormative ijuridical iresearch imethod.Data icollection itechniques iwith ilibrary istudies. iThe idata ithat ihas ibeen iobtained iis ithen ianalyzed iqualitatively ito iobtain idescriptive iresearch iresults. iBased ion ithe iresults iof ithe istudy, iit iis iknown ithat ithe iurgency iof iextending ithe iterm iof iNotary iOffice iin iIndonesia ihas imet ithe iprinciple iof irationality, ithe iconsideration iof ijudges iin ithe idecision iof ithe iConstitutional iCourt iNumber: i84/PUU-XXII/2024 iconcerning ithe iage ilimit iof iNotaries ihas imet ithe iprinciple iof irationality, iaccording ito ithe icourt, ithe iextension iof ithe iterm iof iOffice iof iNotaries iwill ibe irational iif ithe ilimit iis imore ithan i67 iyears iold, iwhich iaccording ito ithe icourt iis irational iup ito ia imaximum iage iof i70 iyears iby ireferring ito ithe iaverage iretirement iage iof iother isimilar ipositions. iWith ithe iextension, iit iis iexpected ithat inotaries ican istill imeet itheir ineeds iuntil ithe iage iof i70 ias ilong ias ithey iare iphysically iand ispiritually ihealthy ito icarry iout itheir iduties iproperly. iKeywords: iNotary, iRasionality iand iRetirement iAge.